Design, synthesis, and biological investigation of oxadiazolyl, thiadiazolyl, and pyrimidinyl linked antipyrine derivatives as potential non-acidic anti-inflammatory agents. (31st December 2023) - Al-Sanea, Mohammad M.; Hamdi, Abdelrahman; Brogi, Simone; S. Tawfik, Samar; Othman, Dina I. A.; Elshal, Mahmoud; Ur Rahman, Hidayat; Parambi, Della G. T.; M. Elbargisy, Rehab; Selim, Samy; Mostafa, Ehab M.; Mohamed, Ahmed A. B.
Abstract: A novel series of 12 antipyrine derivatives containing 1, 3, 4-oxadiazoles (4a-d), 1, 3, 4-thiadiazoles (6a -d), and pyrimidines (8a -d), was preparedand assessed for its potential in vitro COX-2 inhibitors. Compared to Celecoxib, compounds 4b-d and 8d were the most potent derivatives c with a half-maximal inhibitory concentration range of 53–69 nM. Considering COX-2 selectivity index, compounds 4 b and 4c were chosen among these most potent derivatives for further investigation. The in vivo ability of compounds 4 b and 4c to counteract carrageenan-induced paw edoema has been assessed and their potential underlying mechanisms have been elucidated and the results have been further validated using molecular docking simulations.